Information frictions and the two margins of trade: Evidence from Slovenian manufacturing - Elena Zaurino; Saéso Polanec (European Commission, 2023)
We empirically investigate whether firms lower information frictions in foreign sourcing through prior exporting. Using a panel of Slovenian manufacturing firms in the period 1996-2011, we estimate the probability of import entry in a new market when the firm is already exporting to the same country and we find a positive and significant relation. To control for the endogeneity of the export decision, we implement an instrumental variable approach exploiting the notion of sequential exporting. Moreover, we rule out productivity growth as being the only predictor of entry in a foreign market through several falsification tests. These findings suggest information frictions play an important role for firms trading in international markets.
Keywords: F14; L20; D22; D83; 330; Sourcing; Import entry; Information Frictions; Sunk costs